Aktualisasi Teologi al Ma'un Dalam Kegiatn Ekstrakurikuler Palang Merah Remaja Di SMP Negeri 1 Surakarta Tahun 2015-2016 - Khoiruddin, Imam, Dr. Waston, M.Hum, Dr. M. Muhtarom, SH. MH (2017)
The worship activities is very closely related to social activities. Al ma'un is one of letter that explaine about the ritual of worshiping in social activities. This study aims to describe the theology of Al ma'un as well as describe the actualization ofAl ma'un'stheology that executedofextracurricular PMR activities of Public's Junior High School number 1of Surakarta. The research method used to get the data usesofthe qualitative method with data collection techniques in the form of interviews that are validated by observation, and documentation. The research results that obtained from this study are Al ma'un'stheology is the of applyingtheology that do not merely memorized, read and understood.Basic assumptions of the al 'un'stheology is a worship activity that requires the concrete action that related to social problems. PMR of Public's Junior High School number 1of Surakartatries to actualize Al ma'un's theology with a capacity of its own capabilities. Activities that conducted by PMR of of Public's Junior High School number 1of Surakartainform of capabilities within to execute the fundamental social activities. Capabilities that possessed just limited as training and conditioningsite. In addition also need the guidance and mentoring. Actualizing Al ma'un's theology that conducted by members of the PMR ofPublic's Junior High School number 1there are several servicesdomain.Service from of schooling (education) domain is done with training activities about social material of the Red Crossing. The charity service conducted with activities of humanity wallet with objective the poor and displaced person. The activities of Character building camp is a service from of healing and feeding because it teaches the students to attempt to have socialize as well as provide care for others that need it.